Radiometric dating and stratigraphic reassessment of the Elliot and Clarens formations; near Maphutseng and Moyeni, Kingdom of Lesotho, southern Africa - Rademan, Zandri (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2019.